European evidence based consensus on the diagnosis and management of Crohn's disease: special situations. (15th February 2006) - Caprilli, R; Gassull, M A; Escher, J C; Moser, G; Munkholm, P; Forbes, A; Hommes, D W; Lochs, H; Angelucci, E; Cocco, A; Vucelic, B; Hildebrand, H; et al.
Abstract : This third section of the European Crohn's and Colitis Organisation (ECCO) Consensus on the management of Crohn's disease concerns postoperative recurrence, fistulating disease, paediatrics, pregnancy, psychosomatics, extraintestinal manifestations, and alternative therapy. The first section on definitions and diagnosis reports on the aims and methods of the consensus, as well as sections on diagnosis, pathology, and classification of Crohn's disease. The second section on current management addresses treatment of active disease, maintenance of medically induced remission, and surgery of Crohn's disease.